Day 3 Wed, February 22, 2017 2017
DOI: 10.2118/182719-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drill and Learn: A Decision Making Workflow to Quantify Value of Learning

Abstract: The goal of reservoir management is to make decisions with the objective of maximizing the value creation from the oil or gas production. In order to do this models that preserve geological realism and have predictive capabilities are being developed and used. These models are commonly calibrated by using Assisted History Matching (AHM) methods which, in general, will lead to reduced uncertainty in the predicted production. Although uncertainty assessment and reduction is often an element of high-quality decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In Eq. 19, σ 2 α is an estimate of the variance of α over the domain of interest, σ 2 β is the variance of β, and n eff is the effective sample size for the observations of β (18). The regularized estimate,α r (x i ), is obtained by solving ∇ α S = 0, obtaining:…”
Section: Distance-based Localizationmentioning
confidence: 99%
“…In Eq. 19, σ 2 α is an estimate of the variance of α over the domain of interest, σ 2 β is the variance of β, and n eff is the effective sample size for the observations of β (18). The regularized estimate,α r (x i ), is obtained by solving ∇ α S = 0, obtaining:…”
Section: Distance-based Localizationmentioning
confidence: 99%
“…As discussed in Introduction, recent work that applied modified versions of CLFD (Morosov and Schiozer, 2016;Hanea et al, 2017), reported that application of CLFD, in some cases, has resulted in slight reduction of true-model NPV. It may seem counter-intuitive that assimilating new data and re-optimizing decision variables over the remaining span of project life, in cases has lead to a decrease in true-model NPV (which is the ultimate outcome).…”
Section: Trumap: True-model-based Assessment Of Performancementioning
confidence: 99%
“…The use of multiple true-models in CLFD has also been considered by Hanea et al (2017) and Shirangi and Durlofsky (2015). Hanea et al (2017), however, did not present a procedure for performance assessment (as TruMAP) and used too few cases.…”
Section: Trumap: True-model-based Assessment Of Performancementioning
confidence: 99%
See 2 more Smart Citations